2017
DOI: 10.12669/pjms.331.10386
|View full text |Cite
|
Sign up to set email alerts
|

Labour induction with Gestational Hypertension: A great obstetric challenge

Abstract: Objective:To observe the fetomaternal morbidity and mortality with induction of labour in pregnant women with gestational hypertension.Methods:The subjected study population included was 138 pregnant women with gestational hypertension. These pregnant women were between 34-40 weeks of gestational period in whom labour was induced, while the pregnant women who had labour induction for other reasons were excluded. These women were registered on the predesigned proforma. The data was collected and analyzed on SPS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
(12 reference statements)
2
3
0
Order By: Relevance
“…In the study by Khaskelil et al majority (51.4%) of preeclamptic women were admitted at 35-38 weeks of gestation which is consistent with the present study [6] .…”
Section: Booked/unbookedsupporting
confidence: 92%
See 1 more Smart Citation
“…In the study by Khaskelil et al majority (51.4%) of preeclamptic women were admitted at 35-38 weeks of gestation which is consistent with the present study [6] .…”
Section: Booked/unbookedsupporting
confidence: 92%
“…In the study by Khaskheli et al it was observed that that 20% of preeclamptic women had undergone induction out of which 64.49% women had normal vaginal delivery and 28.3%women had LSCS. Failed induction occurred in 30.76% women [6] .…”
Section: Mode Of Deliverymentioning
confidence: 98%
“…In the present study, when the baseline characteristics were compared it was seen that the mean age and parity were similar in both Group A and Group B which was similar to the study conducted by Pallipuram et al and Khaskheli MN et al, and also HYPITAT trial. 4,7,8 In the present study gestational hypertension was seen more in unbooked cases (68.33% in group A and 70% in group B). Bangal VB et al, also found that 80% of the patients were unbooked.…”
Section: Discussionsupporting
confidence: 49%
“…Women with HDP have significantly higher probability of adverse maternal and fetal outcomes than normal pregnant women. 6 Stratified management of maternal risk factors can help to identify highrisk pregnant women in a timely manner and ease the socioeconomic burden on the patients and on the healthcare system. Currently, SMM is considered the most important indicator of maternal management quality.…”
Section: Discussionmentioning
confidence: 99%